Inhale exhale 2021 opener: Radical pleasure with Ericka Hart - Across Boundaries (2021)
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; corps; cours; discours dominant; fem3300; genre; identités LGBTQIA2+; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sex-positivity; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap